LEXICO-SEMANTIC FEATURES OF CULTURAL SCRIPTONYMS: (Based on Local Ritual Ceremonies). - Akegozhayeva, R. N.; Murzinova, A. S. (Eurasian Journal of Philology: Science & Education, 2025)
The article discusses the lexical and semantic features of scriptonyms in the cultural code, which are formed on the basis local ritual ceremonies. The study aims to analyze the lexical and semantic specificity of secondary-meaning scriptonyms that originate from regional ritual ceremonies. Information related to regional procedures is transformed into linguo-cultural codes, aiding in the identification of the uniqueness of regional ethno-linguistic consciousness and the decryption of encoded information within these codes. This demonstrates the originality of our research. The scientific significance of the research lies in separately considering linguistic units (scriptonyms) formed on the basis of local rituals. To identify the diatopic (local) variants of scriptonyms, the article compared and studied the rituals and sacred names that originating from four regions of Kazakhstan: South, East, West, and Central Kazakhstan. It was found that the depiction of the universe in a regional language is influenced by the characteristics of the geographical area, the customs of the people, and the mutual cultural influences of ethnic groups. The scriptonyms, linguocultural, and conceptual concepts formed based on local ritual ceremonies analyzed in the research can serve to elucidate the etymology of native words in the Kazakh language and aid in the development of dialectological dictionaries. This demonstrates the value and practical significance of the study. Through the research: the relationships and distinctions between the concepts of tradition, customs, and ritual ceremonies were delineated; the term “code” was examined from a linguocultural perspective; ritual ceremonies were explored as a pivotal source in shaping cultural codes (scriptonyms) with substantial informational influence; and the characteristics of regional ethnolinguistic consciousness were elucidated through the analysis of scriptonyms derived from local ritual ceremonies. The article employs qualitative analysis, including content analysis, to examine and reveal the etymology of the linguistic units of the sacred code that have developed in relation to rituals.